Navigating brand equity in personal care: Examining the influence of direct-to-consumer brands and the mediating power of brand image - Modi, Shailavi; Balaji, Vedha; Mathew, Sonia; Kishore, Krishna (International Journal of Management and Sustainability, 2024)
The COVID-19 pandemic triggered consumers to buy products online, leading to unprecedented and unforeseen growth in the e-commerce sector. Therefore, the revolution made by Direct-to-consumer (DTC) brands went unnoticed. Unlike the conventional approach, which took years to build brand trust and equity, the DTC business model allows companies to grow exponentially with their presence in personal care online marketplaces. Therefore, the rise of DTC brands empowers small and medium enterprises (SMEs) and micro small and medium enterprises (MSMEs) in India, mainly because the return on ad spend (ROAS) for these brands is a huge problem when compared to giant companies. Also, branding in tier 2 and tier 3 markets has triggered new hurdles as consumers need to build brand trust to pay or transact online. The present research examines how a DTC website and electronic word-of-mouth (eWOM) can enhance the effectiveness of branding for direct-to-consumer brands. The study employed a quantitative methodology by analyzing the survey-based research design, with 389 respondents who were aware of and/or used DTC personal care brands in India participating. The present study’s findings demonstrate that website attractiveness and electronic word-of-mouth enhance DTC brands and minimize costs developed to advertise a product, increasing ROAS. Further research studies would broaden DTC brands' knowledge by investigating the impact of e-commerce and social media channels on enhancing consumers' brand equity or purchase intention.